The Impacts of Perceived Risks on Information Search and Risk Reduction Strategies: A Study of the Hotel Industry during the COVID-19 Pandemic - Yi-Wei Zhang (MDPI AG, 2021)
This study examined the impacts of perceived risks on information search and risk reduction strategies as well as the relative importance of each risk reduction strategy. Multiple regression analysis was applied to analyze the sample of South Korean hotel customers and to test the hypotheses of the study. It was found that when hotel customers faced the same kind of risk, they adopted different information search strategies to reduce various risks during the COVID-19 pandemic. Moreover, ‘following hotel employee’s advice’ was perceived to be the most important information search strategy to reduce risks. This is the first study to compare the differences of perceived risk and information search strategies under the COVID-19 pandemic and normal conditions to help hotels to develop more effective strategies to recover from the pandemic. The results of the study should be interpreted with care since it was based on Korean hotel customers. The influence of cultural differences in perceived risk and information search strategy should be addressed in future studies. The study contributes to the tourism and hospitality information search and risk reduction strategy-related literature and recommends avenues for further research in the field.